THE INFLUENCE OF SUPERVISION AND COMPLIANCE WITH PROCUREMENT REGULATIONS ON THE EFFICIENCY OF REGIONAL GOVERNMENT SPENDING IN NORTH MINAHASA REGENCY - Rizky Rachel Widagdo; Wilson Bogar; Recky H. E. Sendouw (PT. Radja Intercontinental Publishing, 2026)
This study aims to describe, analyze, and interpret the effect of supervision and compliance with procurement regulations on the spending efficiency of the Regional Government of North Minahasa Regency, both partially and simultaneously. This research employs a quantitative approach using a survey method by distributing questionnaires to 33 respondents who are government officials involved in financial management and public procurement processes. The data were analyzed using multiple linear regression techniques with the assistance of IBM SPSS version 26. The results indicate that, partially, the supervision variable has a positive and significant effect on spending efficiency, with a t-value of 4.106 and a significance level of 0.002. Similarly, compliance with procurement regulations also shows a positive and significant effect on spending efficiency, with a t-value of 3.104 and a significance level of 0.004. Simultaneously, both independent variables significantly influence spending efficiency, as indicated by an F-value of 4.917 and a significance level of 0.014. Furthermore, the coefficient of determination (R²) is 0.247, which means that supervision and regulatory compliance jointly contribute 24.7% to the variation in spending efficiency, while the remaining 75.3% is explained by other factors outside the research model. These findings suggest that strengthening supervision mechanisms and improving compliance with procurement regulations are critical factors in enhancing regional spending efficiency.